ASME 2007 Energy Sustainability Conference 2007
DOI: 10.1115/es2007-36151
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Efficiency of the Advanced Injection Low Pilot Ignited Natural Gas Engine Using Organic Rankine Cycles

Abstract: Intense energy security debates amidst the ever increasing demand for energy in the country have provided sufficient impetus to investigate alternative and sustainable energy sources to the current fossil fuel driven economy. This paper presents the Advanced injection Low Pilot Ignition Natural Gas (ALPING) engine as a viable, efficient and low emissions alternative to conventional diesel engines, and discusses further efficiency improvements to the base ALPING engine using Organic Rankine Cycles (ORC) as bott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…Recently, it has been used widely as small compact cogenerative plant using biomass and waste heat [2][3][4][19][20][21][22][23][24]. Other interesting applications regard the efficiency improvement of internal combustion engines using ORC as bottoming cycles, both for small size engines for automotive use [25][26][27][28] and for large size engines for industrial and marine use [29,30]. A simplified schematic of an ORC plant is presented in Fig.…”
Section: The Orc Technologymentioning
confidence: 99%
“…Recently, it has been used widely as small compact cogenerative plant using biomass and waste heat [2][3][4][19][20][21][22][23][24]. Other interesting applications regard the efficiency improvement of internal combustion engines using ORC as bottoming cycles, both for small size engines for automotive use [25][26][27][28] and for large size engines for industrial and marine use [29,30]. A simplified schematic of an ORC plant is presented in Fig.…”
Section: The Orc Technologymentioning
confidence: 99%
“…Krishnan et al [11] (see Fig. 1) and Srinivasan et al [12,13] demonstrated that ultra-low engine-out NO^ emissions (less than 0.2 g/kWh without any exhaust after treatment) with diesel-equivalent fuel conversion efticiencies (about 40%) were possible with the advanced injection low pilot ignition natural gas (ALPING) dual fuel combustion strategy. The ALPING combustion concept employs very early injection (approximately 60 deg BTDC) of small diesel pilots (1-5% on an energy basis) to ignite lean premixed natural gas-air mixtures.…”
Section: Introductionmentioning
confidence: 98%
“…This examination quantified the potential improvements in fuel conversion efficiency (FCE) and brake specific emissions (NOx and CO2) with hot exhaust gas recirculation (EGR) addition and waste heat recovery using ORC turbocompounding. Their another related work estimated that ORCturbocompounding results in FCE improvements of 10% while maintaining the essential low NOx characteristics of ALPING combustion [14]. B. Yao [16]designed a dual loop organic Rankine cycle system for waste heat recovery of a heavy-duty compressed natural gas (CNG) engine, in which cycle R245fa was used as the working fluid.…”
Section: Introductionmentioning
confidence: 99%
“…There are only a few works concerning about ORC combining natural gas engines [13][14][15][16][17]. K. K. Srinivasan et al [13] examined the EWH recovery potential from an advanced Low Pilot Ignited Natural Gas (ALPING) low temperature combustion using a bottoming ORC.…”
Section: Introductionmentioning
confidence: 99%